Trinity Cathedral, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (Muir, Marshall and Co., Trinidad, 2010)
Image depicts a view of the Trinity Cathedral, located in Port of Spain, Trinidad, in the twin-island Republic of Trinidad and Tobago. The view is from Woodford Square looking southward, and the cathedral's facade is partly obscured by trees.
Colour: Shades of red, green, brown, blue and white; Style: Landscape; Other: Unbordered, Divided.
Keywords: Trinidad and Tobago; Postcards; Cathedrals; Buildings; Port of Spain